One-pot synthesis of uniform and monodisperse superparamagnetic molecularly imprinted polymer nanospheres through a sol–gel process for selective recognition of bisphenol A in aqueous media. Issue 70 (12th July 2016) - Chang, Tingting; Liu, Yuxin; Yan, Xiangyang; Liu, Shaomin; Zheng, Haisong
Abstract : Uniform and monodisperse Fe3 O4 @MIP nanospheres were directly synthesized using a sol–gel method on the surface of Fe3 O4 –COOH spheres. Abstract : In this study, a facile method was used to synthesize core–shell magnetic surface molecularly imprinted polymer (Fe3 O4 @MIP) nanospheres. Initially, monodisperse carboxyl-functionalized Fe3 O4 nanoparticles (Fe3 O4 –COOH) were obtained through a one-step hydrothermal method, the imprinted layer was then synthesized directly on the surface of the magnetic core via a one-pot sol–gel method. The morphology and structural properties of the prepared magnetic nanoparticles were characterized by XRD, TEM, SEM, FT-IR and VSM. The synthesis conditions for the formation of Fe3 O4 @MIPs were systematically investigated. It was found that the monodispersity and morphology of Fe3 O4 @MIPs were highly influenced by the concentration of ammonium hydroxide (NH3 ·H2 O), the solvent composition (methanol–water), and the molar ratio of functional monomer and cross-linker. Interestingly, the preparation process of the Fe3 O4 @MIPs was direct and simple without further complex modification on the surface of Fe3 O4 compared with conventional imprinting methods, which makes the saturation magnetization value for the Fe3 O4 @MIPs samples higher than those of common obtained materials. Meanwhile, the entire process of sol–gel polymerization was shortened to 1 h, which was much shorter than typical polymerization times. The adsorption performances of Fe3 O4 @MIPs and Fe3 O4 @NIPs with optimized morphologies were evaluated in bisphenol A (BPA) aqueous solution. The results showed that the product had the advantages of large adsorption capacity, good selectivity and favourable reusability, which are ascribed to its high uniformity and monodispersity. In addition, the molecular recognition of the obtained Fe3 O4 @MIPs was realized in aqueous media, which is conducive to practical applications on a larger scale and makes Fe3 O4 @MIPs an ideal adsorption and enrichment material.